Treatment Tactics Of Sepsis In Purulent-Necrotic Diseases Of Soft Tissue - Abdullaev Rasuljon Nabievich; Abdullaeva Malika Azimovna (Genius Publishing Group, 2024)
The article analyzes the work carried out to create a new algorithm for the diagnosis and complex treatment of sepsis in patients with purulent-necrotic diseases of soft tissues. In the departments of purulent surgery of the ASMI clinic and the regional adult health center of the Andijan region, 28 patients with purulent-necrotic diseases of soft tissues underwent a study, where the tasks were set to create a new step-by-step algorithm for the diagnosis and complex treatment of sepsis in patients with purulent-necrotic diseases of soft tissues.
Keywords: Sepsis; purulent-necrotic diseases of soft tissues; facial carbuncle